“Will the dream continue, until you understand its message?”- postmodern love : a constructed verisimilitude of reality in Bornholm Night-Ferry - Wai, Serina Ke Xin (2011)
This paper provokes discerning readers to question the verity of the external world. Aidan Higgins’ Bornholm Night-Ferry envelops readers into a microcosm of two people who, through their psychologically precise love letters, shared a tumultuous love affair. The epistolary structure of the novel provokes a defamiliarization of reality as we know it by unraveling a space where the derivation of reality is from the language used by the two lovers to express their love. While Higgins begins to combat the implications arose from the attempts at expressing love, he evokes the multiplicities of one’s consciousness of reality where his preconceived ideas are dispositioned and replaced by the reality offered in the novel. This paper posits that nothing is rational in the love letters of Bornholm Night-Ferry as to be rational is to dismiss the sensualism that is waiting to be unleashed unto its intended recipient. Despite an absence of a union between life and mind, the trick to sustain the verities that both entities present is to ruminate in their momentous collisions. The sensual is then derived from such an occurrence where one can then establish a reality that is true to him. Higgins pushes for the ability for the sustenance of an alternate reality through an illustration of a love that is consummated through language alone. Higgins not only establishes the concept of love a basis for the manifestation of an invented world, he also challenges the expressibility of love and ultimately succeeds in establishing the need for man to acknowledge his innate multiplicity of consciousness with regards to his perception of reality.